DETERMINAN PEMANFAATAN PMK 44 INSENTIF PAJAK OLEH WAJIB PAJAK UMKM (Studi Kasus Pada UMKM Yang Terdaftar Di KPP Malang Utara) - Zuhrotun Nisa; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The Covid-19 pandemic is still a hot topic of discussion even though 8 months have passed since the start of the Covid-19 virus entering Indonesia and the government has established a covid response situation since March 2, 2020. Various policies have been carried out by the government to prevent transmission. vírus Covid-19 massively. One of them is by limiting activities to leave the house. Over time, policies to limit the mobility of residents such as large-scale social restrictions (PSBB) in several areas have had a very visible impact on the economic sector. In order to save the country's economy, the government issued a new life order policy or the so-called “new normal era”. The government continues to strive to restore the economy of society, one of which is in the Micro, Small and Medium Enterprises (MSMEs) sector. For this reason, one of the policies issued by the government is Supporting recovery is by issuing PMK No. 44/03/2020 concerning Tax Incentives for Taxpayers Affected by the Corona Virus Disease 2019 Pandemic.The type of research used is correlational research, namely research that tests hypotheses using a quantitative approach. There is an effect of tax socialization, knowledge and understanding of taxation. as well as ease of taxation services for the Use of PMK 44 of 2020.Keywords : MSMEs, tax incentives, PMK 44, tax socialization, tax knowledge and understanding, ease of tax services, utilization of tax incentives